Pengaruh Kejelasan Sasaran Anggaran Komitmen Organisasi Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Se-Kecamatan Mengwi - Wayan Sri Aryan Tini; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2026)
Accountability is very necessary as a form of accountability of the village government to the community. The community is not only given information about the existence of the village budget, but also must be given a report. Accountability related to the realization of the budget. This study aims to examine the effect of clarity of budget targets, organizational commitment and community participation on the accountability of village fund management in Mengwi sub-district. The number of samples used in this study was 112 respondents using a purposive sampling method. Data collection was carried out using a questionnaire. Data analysis techniques used in this study were descriptive statistics, validity test, reliability tests, normality tests, multicolinearity tests, heteroscedasticity tests, multiple linear analysis, coefficient of determination (R), f tests. The results of the study indicate that clarity of budget targets, organizational commitment and community participation have a positive and significant influence on accountability in village fund management.